UBUNGAN TINGKAT PENGETAHUAN PHBS (PERILAKU HIDUP BERSIH DAN SEHAT) TERHADAP KEJADIAN SCABIES PADA SANTRIWAN DI PONDOK PESANTREN NURUL ISLAM KECAMATAN SUMBERSARI - Mahmud Ady Yuwanto; Ahmad Efrizal Ammrullah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2017)
The incidence of diseases and health problems in humans is inseparable from the role of environmental factors. The purpose of this study was to identify the relationship of the level of knowledge (PHBS) to the incidence of scabies in students at the boarding school Nurul Islam Sumbersari District, Jember Regency. This type of research uses analytic survey research with cross sectional design. The population in this study were 113 respondents who were in Nurul Islam Islamic Boarding School, Sumbersari District, Jembar Regency. The samples in this study were 88 respondents with simple random sampling technique. The level of knowledge is good (25%), sufficient (29.5%), lacking (45.5%) and the incidence of scabies of Satriwan experiencing scabies (55.7%), which is not (44.3%). Chi square test results Relationship between PHBS Knowledge Level and Scabies Occurrence in queues with p value 0,000 there is a significant relationship between students' PHBS knowledge and scabies events. The higher the knowledge the lower the incidence of scabies. It is recommended in this study that students apply healthy hygienic behavior to increase PHBS knowledge on the incidence of scabies, and boarding schools to be able to provide facilities and infrastructure for healthy and clean environmental sanitation in boarding schools